Influência do ciclo estral no diâmetro oocitário em cadelas - Pereira, L. M.C. [UNESP]; Bersano, P. R.O. [UNESP]; Lopes, M. D. [UNESP] (My University, 2013)
The objective of this study was to evaluate the relationship between the phases of diestrus and anestrus, with oocyte diameter of bitches. A total of 41 female dogs, subject to ovariohysterectomy (OSH) elective in the Clinic of Small Animal Reproduction FMVZ / UNESP, Botucatu. The ovaries were sectioned and selected only the cumulus-oocyte complexes (COCs) grade I, which were submitted to the solution of hyaluronidase of 2% and stained with Hoechst. The results showed no difference (p>0,05) between the mean diameter of oocyte and the phase of the estrous cycle.
Influence estrous cycle bitches in diameter oocyte
Keywords: Bitches; Diameter; Estrous cycle; Oocyte